Leveraging Machine Learning and Open Data for Smart Cities - Salon, Data; Salon, Data (Data Science Salon, 2020)
Presented by Priscilla Boyd - Senior Manager, Data Analytics at Siemens Mobility This presentation discusses how AI, machine learning and data publicly available is playing a role in smart cities, walking through applications developed using ML to solve practical transportation for smart cities globally.